Identification of Priority Sites to Support Management of Commercially Important Sea Cucumber Species by Applying Infomap and Habitat Filters to Larval Dispersal Data - Deauna, Josephine Dianne L.; Yatco, Kevin Matthew B.; Villanoy, Cesar L.; Juinio-Meñez, Marie Antonette (Frontiers in Marine Science, 2021)
Stocks of commercially valuable sea cucumber species have declined in most tropical countries, which supply majority of the global demand. This work aimed to locate priority sites for the management of Holothuria scabra and Stichopus horrens in the western central Philippines. A passive larval dispersal model was run under four monsoonal regimes (Northeast monsoon, dry-transition, Southwest monsoon, and early Northeast monsoon), and the results subjected to the Infomap network detection algorithm. Three clusters of closely related geographical nodes were identified [southeastern Palawan (Group I), western Panay and eastern Mindoro (Group II), and northern and western Palawan with western Mindoro (Group III)]. Remotely sensed habitat data were used to parameterize the degree of connectivity observed among sites (H. scabra spawning and settlement requires the presence of seagrass and mangrove, while S. horrens requires corals and seagrass). Local retention, self-recruitment, settlement success and sink diversity were then calculated for each node with suitable habitat. The locations were ranked according to each metric and those with higher larval export rates, a higher diversity of larval sources and a high degree of successful larval contribution to other sites were deemed crucial for the management of wild populations. Sixteen high-priority sites were identified, distributed mainly along northern Palawan and western Panay. Six sites were common for both species at different seasons, and no single location fulfilled all stated criteria across the four seasons and both sea cucumber species considered. The priority sites for management could serve as broodstock selection and juvenile restocking areas for aquaculture production clusters, which when properly implemented, could lead to an increase in sea cucumber production and contribute to natural populations. On a broader scale, the designation of closely related clusters and incorporation of habitat requirements to dispersal data provided critical input for the delineation of ecologically meaningful management units for sea cucumbers within the region.